1966
DOI: 10.1037/h0023309
|View full text |Cite
|
Sign up to set email alerts
|

Sources of behavioral variance as measured by the S-R Inventory of Anxiousness.

Abstract: A reanalysis, which partitions the proportions of variance from the various main sources and their interactions, of previously reported data from the S-R Inventory of Anxiousness and from a new sample, suggests that the debate over the relative importance of individual differences and of situations is largely a pseudoissue. While it is true that the mean squares for situations are regularly much larger than the mean squares for individual differences, a partitioning of the variance shows, at least for the trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(159 citation statements)
references
References 32 publications
6
153
0
Order By: Relevance
“…Table 4 presents the correlations of FNE and SAD with Taylor's (1953) Manifest Anxiety (MA) scale, Rotter's (1966) Locus of Control scale (LC), Alpert and Haber's (1960) Achievement Anxiety scale, divided into debilitating and facilitating anxiety subscales (AH-and AH+), the social and evaluative parts of the Endler-Hunt (1966) S-R Inventory of Anxiousness (E-H), Paivio's (196S) Audience Sensitivity Index (ASI), and 11 of the subscales of Jackson's (1966aJackson's ( , 1966b Personality Research Form (Social Approval, Affiliation, Desirability, Autonomy, Defendence, Achievement, Aggression, Dominance, Abasement, Exhibitionism, and Impulsivity), The table presents only significant or borderline correlations.…”
Section: Correlational Studiesmentioning
confidence: 99%
“…Table 4 presents the correlations of FNE and SAD with Taylor's (1953) Manifest Anxiety (MA) scale, Rotter's (1966) Locus of Control scale (LC), Alpert and Haber's (1960) Achievement Anxiety scale, divided into debilitating and facilitating anxiety subscales (AH-and AH+), the social and evaluative parts of the Endler-Hunt (1966) S-R Inventory of Anxiousness (E-H), Paivio's (196S) Audience Sensitivity Index (ASI), and 11 of the subscales of Jackson's (1966aJackson's ( , 1966b Personality Research Form (Social Approval, Affiliation, Desirability, Autonomy, Defendence, Achievement, Aggression, Dominance, Abasement, Exhibitionism, and Impulsivity), The table presents only significant or borderline correlations.…”
Section: Correlational Studiesmentioning
confidence: 99%
“…But the data indicate that neither of these extreme viewpoints is supported. In a number of studies the average amount of variance attributable to persons is in the order of five percent, and the amount of variance due to situations is similar (Endler and Hunt 1966). Interactions between persons and situations, however, did account for comparatively large amounts of variance .…”
Section: Findings and Discussionmentioning
confidence: 89%
“…The author chose to develop scale items related to specific computer experiences because anxiety scale development indicated that scale items referring to specific situations have better predictive validity than do items with more general content (Endler & Hunt, 1966). The 20 scale items were chosen from a set of 54 items by a panel of professors who used computers in their courses.…”
Section: Marcoulides: Computer Anxiety Scale (Cas-m)mentioning
confidence: 99%